2009
DOI: 10.1136/bmj.b2546
|View full text |Cite
|
Sign up to set email alerts
|

Cytological surveillance compared with immediate referral for colposcopy in management of women with low grade cervical abnormalities: multicentre randomised controlled trial

Abstract: Objectives To examine the effectiveness of cytological surveillance in primary care compared with immediate referral for colposcopic examination in women with low grade abnormal results on cervical cytology tests. Design Multicentre individually randomised controlled trial. Setting NHS cervical screening programmes in Grampian, Tayside, and Nottingham. Participants 4439 women, aged 20-59, with a cytology result showing borderline nuclear abnormalities or mild dyskaryosis, October 1999-October 2002. Interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…These women would have experienced excision or ablation of abnormalities as necessary, and were recorded at approximately nine months post-event [19,20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These women would have experienced excision or ablation of abnormalities as necessary, and were recorded at approximately nine months post-event [19,20]. …”
Section: Methodsmentioning
confidence: 99%
“…These women were under routine cytological surveillance following abnormal cytology, which had occurred up to one year prior to HRQL measurement [19,20]. …”
Section: Methodsmentioning
confidence: 99%
“…In the large, population-based, randomised controlled trial known as TOMBOLA, nested within the UK NHS Cervical Screening Programmes (CSP), in which women were followed for three years after receipt of low-grade abnormal cytology, we found that CIN2/3 was detected earlier in women undergoing immediate colposcopy. However, the cost-effectiveness of the alternative management approaches did not differ, and immediate colposcopy was associated with higher levels of physical after-effects [15], [16]. Making informed choices between such alternatives requires a full understanding of the advantages and disadvantages of each policy but, so far, evidence on the psychological impact on women is limited; most studies have been small, considered only one management strategy and/or were not randomised.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, some authors advocate a more conservative approach to LSIL cytology and propose cytological follow-up with or without HPV testing. 5,[8][9][10][11] The morphology of LSIL includes a range of cellular changes from koilocytic atypia with slight nuclear changes to clearly dysplastic cells with dyskaryotic nuclei and abundant cytoplasm. 12 Koilocytosis is considered to be the cytopathic effect of HPV infection, but is not a necessary feature of LSIL, 13,14 and is more likely to be associated with non-progressive lesions.…”
Section: Introductionmentioning
confidence: 99%